Palliative Care and End-of-Life Issues in Elderly Cancer Patients With Head and Neck Cancer - Schrijvers, Dirk; Charlton, Rodger (Frontiers in Oncology, 2022)
The number of elderly patients with incurable head and neck cancer will increase. They are in need of geriatric palliative care, that takes into account oncology, palliative care and geriatric medicine. In this review, several physical problems (e.g. pain, fatigue, malnutrition, and loco-regional problems) encounter by the elderly head and neck cancer patients are addressed. In addition end-of life issues in this patient population are discussed.